FONOLOGI BAHASA KANAUMANA KOLANA - Lodia Amelia Banik (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2017)
This research entitled is Phonology of Kanaumana Kolana Language. The purpose of this study was to describe the system of phonemes and describe the phonological processes found in Kanaumana Kolana language. The method used in this research was descriptive qualitative method. Data collected in the form of the sounds of language Kanaumana Kolana obtained from interviews with native speakers Kanaumana Kolana. Based on the research results Language Kanaumana Kolana had six vowels were vowel /i/, /u/, /e/, /É›/, /o/ and /a/, thirteen consonant, the consonant resistor: /p, b, t, d, j, k, g/, consonant fricatives: /s/, consonant nasal: /m, n, Å‹/, consonant liquid or lateral: / l /, consonant trill / r / and two semi-vowels: / y, w /. The existence of the six vowels, twelve consonant and two glides supported by evidence using minimal pairs at the time to identify sounds such phonemes in a language Kanaumana Kolana. Phonological processes found in Kanaumana Kolana language there were two, they were the deletion process syllable structure and deletion processes accompanied by changes in the structure of the syllable form phonemes sound changes. The phonological processes found during the two segments combined into one segment. Keywords: phoneme, phonological process, ruling